Studi Kasus Masalah Keperawatan Menyusui Tidak Efektif pada Ibu Post Partum - Wulandari, Yuanita; Priyantini, Diah; Supatmi , Supatmi; Aviari, Vira Aulia (Universitas Muhammadiyah Surabaya, 2022)
Background: Ineffective breastfeeding is a condition where the mother and baby experience dissatisfaction with the breastfeeding process. This is due to the health condition of the mother and baby, wrong position and technique, lack of breast milkproduction, breast disease or infection. So there is a need for breastfeeding education, such as providing support to mothers to increase their confidence in breastfeeding. The aim of this research is to identify the problem of ineffective breastfeeding nursing in postpartum mothers. Method: qualitative descriptiveresearch with a case study approach using the nursing process to explore the signs and symptoms and etiology of ineffective breastfeeding in postpartum mothers. This case study used 5 respondents with ineffective breastfeeding nursing problems. Results and Discussion: The results of this study showed 5 (83%) major signs in 4respondents and 6 (100%) major signs in 1 respondent. Meanwhile, 4 (80%) minorsigns were found in 5 respondents. The factors causing the problem of ineffective breastfeeding nursing were breast anomalies (inverted nipples) in 2 respondents, swollen breasts, inadequate breast milk supply and lack of exposure to information.It is hoped that the results of this research will be an additional reference in conducting further studies for the process of enforcing a diagnosis of ineffective breastfeeding nursing